What have we learned from the streptozotocin-induced animal model of sporadic Alzheimer’s disease, about the therapeutic strategies in Alzheimer’s research - Salkovic-Petrisic, Melita; Knezovic, Ana; Hoyer, Siegfried; Riederer, Peter (Journal of neural transmission, 2013)
Experimental models that faithfully mimic the developmental pathology of sporadic Alzheimer’s disease (sAD) in humans are important for testing the novel therapeutic approaches in sAD treatment. Widely used transgenic mice AD models have provided valuable insights into the molecular mechanisms underlying the memory decline but, due to the particular β-amyloid-related gene manipulation, they resemble the familial but not the sporadic AD form, and are, therefore, inappropriate for this purpose. In line with the recent findings of sAD being recognised as an insulin resistant brains state (IRBS), a new, non-transgenic, animal model has been proposed as a representative model of sAD, developed by intracerebroventricular application of the betacytotoxic drug streptozotocin (STZ-icv). The STZ-icv-treated animals (mostly rats and mice) develop IRBS associated with memory impairment and progressive cholinergic deficits, glucose hypometabolism, oxidative stress and neurodegeneration that share many features in common with sAD in humans. The therapeutic strategies (acetylcholinesterase inhibitors, antioxidants and many other drugs) that have been tested until now on the STZ-icv animal model have been reviewed and the comparability of the drugs’ efficacy in this non-transgenic sAD model and the results from clinical trials on sAD patients, evaluated.
Published online: 12 August 2012
Gesehen am 27.01.2022